Genome‐wide copy number analysis on DNA from fetal cells isolated from the blood of pregnant women. (18th November 2016) - Kølvraa, Steen; Singh, Ripudaman; Normand, Elizabeth A.; Qdaisat, Sadeem; van den Veyver, Ignatia B.; Jackson, Laird; Hatt, Lotte; Schelde, Palle; Uldbjerg, Niels; Vestergaard, Else Marie; Zhao, Li; Chen, Rui; et al.
Abstract: Objective: Non‐invasive prenatal testing (NIPT) based on fetal cells in maternal blood has the advantage over NIPT based on circulating cell‐free fetal DNA in that there is no contamination with maternal DNA. This will most likely result in better detection of chromosomal aberrations including subchromosomal defects. The objective of this study was to test whether fetal cells enriched from maternal blood can be used for cell‐based NIPT. Methods: We present a method for enriching fetal cells from maternal blood, subsequent amplification of the fetal genome and detection of chromosomal and subchromosomal variations in the genome. Results: An average of 12.8 fetal cells from 30 mL of maternal blood were recovered using our method. Subsequently, whole genome amplification on fetal cells resulted in amplified fetal DNA in amounts and quality high enough to generate array comparative genomic hybridization as well as next‐generation sequencing profiles. From one to two fetal cells, we were able to demonstrate copy number differences of whole chromosomes (21, X−, and Y) as well as subchromosomal aberrations (ring X). Conclusion: Intact fetal cells can be isolated from every maternal blood sample. Amplified DNA from isolated fetal cells enabled genetic analysis by array comparative genomic hybridization and next‐generation sequencing. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Fetal cells circulating in maternal blood can be enriched with high specificity using markers specific for extravillous trophoblasts. What does this study add? Enriched fetal cells from maternal blood can be used for performing whole genome amplification, followed by array CGH and next generation sequencing paving the way for cell‐based NIPT.